Developing Program Identity and Constituent Support Consistent with Institutional Mission - Thomas R Webster; Traci Ledford (Academic Chairpersons Conference Proceedings, 2016)
Presenters will discuss best practices for building constituent and administrative support for academic programs while simultaneously developing program identity that honors the mission of the institution it represents.
Keywords: Academic Leadership; Program Identity; Institutional Mission; Academic Freedom; Program Support